The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.5334/egems.274
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Prescribing and Dispensing Data of the PCORnet Common Data Model Within PCORnet Antibiotics and Childhood Growth Study

Abstract: Researchers often use prescribing data from electronic health records (EHR) or dispensing data from medication or medical claims to determine medication utilization. However, neither source has complete information on medication use. We compared antibiotic prescribing and dispensing records for 200,395 patients in the National Patient-Centered Clinical Research Network (PCORnet) Antibiotics and Childhood Growth Study. We stratified analyses by delivery system type [closed integrated (cIDS) and non-cIDS]; 90.5 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…This registry captures data on drug dispensing by pharmacies, rather than clinician prescribing, and the 2 metrics may be slightly discordant. 52 , 53 Additionally, the NPA does not include any demographic or diagnostic information about individuals, nor does it include CIs for its projections, although the audit provides a near census of the US retail market. Furthermore, because the NPA categorizes both newly initiated therapy as well as a newly written prescription to continue existing therapy after a patient is completely out of refills as new prescriptions, it was not possible to fully limit our analysis to only those prescriptions that are confirmed new initiations.…”
Section: Discussionmentioning
confidence: 99%
“…This registry captures data on drug dispensing by pharmacies, rather than clinician prescribing, and the 2 metrics may be slightly discordant. 52 , 53 Additionally, the NPA does not include any demographic or diagnostic information about individuals, nor does it include CIs for its projections, although the audit provides a near census of the US retail market. Furthermore, because the NPA categorizes both newly initiated therapy as well as a newly written prescription to continue existing therapy after a patient is completely out of refills as new prescriptions, it was not possible to fully limit our analysis to only those prescriptions that are confirmed new initiations.…”
Section: Discussionmentioning
confidence: 99%
“…One limitation, however, is that we captured antibiotic prescribing data electronically and not based on pharmacy dispensing or claims, which might have led to misclassification of the exposure. However, previous analyses among a subset of participating institutions from PCORnet 24 showed the prescribing data had good sensitivity in identifying patients who filled the antibiotic prescription. Further, we accounted for mostly oral antibiotic prescriptions, although we did capture intramuscular ceftriaxone and penicillin use.…”
Section: Discussionmentioning
confidence: 97%
“…We accounted for duplicated same-day prescriptions and created antibiotic treatment episodes by joining antibiotic prescriptions within 10 days, giving priority to the broadest-spectrum antibiotic prescribed. The PCORnet study group 24 previously compared antibiotic prescription data from electronic health records with pharmacy dispensing records for antibiotics, which showed that misclassification of antibiotic exposure was low. We defined narrow-spectrum antibiotics as penicillin, amoxicillin, and dicloxacillin sodium and broad-spectrum antibiotics as all other antibacterials.…”
Section: Methodsmentioning
confidence: 99%
“…With an eye to what matters to stakeholders-parents and primary physicians-the study also considered whether these findings would influence prescribing patterns and parental expectations; the answer was unambiguously "no" [38]. They were also able to examine data quality by comparing prescriptions and dispensing in 200,395 records and identified gaps in these data, although prescription data were adequate for the question at hand [39]. Finally, in a technical proof of principle, they showed that a form of distributed regression analysis, avoiding the aggregation of patient-level data, generated results comparable to those of the main study [40].…”
Section: Common Data Models Data Quality and Standardsmentioning
confidence: 99%